The optimal taxation of logistics industry in China - Wang Dongmei; Zhou Cairong; Sun Hejie (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: Putting forward policy proposes to improve the tax policy of the logistics industry. Design/methodology/approach: Based on Cobb-Douglas production function model, combined theoretical analysis, this paper puts forward Cobb-Douglas production function expansion model, and using the function estimates the optimal tax burden level of China's logistics industry. Findings: The result of empirical analysis on the state-owned companies and the listed companies of transportation and storage industry show that, the actual tax burden of China's logistics industry is higher than the optimal taxation. This implies that tax problem has restricted the normal operation of the logistics industry in China. Research limitations/implications: Affected by lack of Chinese logistics industry statistics, we only estimate the optimal taxation of state-owned logistics enterprises and listed companies of logistics. But, the two samples are the main force of the logistics industry in China, and the optimal tax calculation result is close, so we can believe that the calculation results are representative. Originality/value: At present, the study of the tax burden on China's logistics industry is almost blank. This research estimates the optimal tax burden level of China's logistics industry, and puts forward recommendations to improve the tax policy of the logistics industry.
Keywords: 650; logistics industry; optimal taxation; production function; China